Magetan Regency MSME Strategy in The New Normal - Sofyan, Mohammad; Fantini, Endah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2021)
This research aims to find problems that often hinder the development of MSMEs in Magetan Regency in the advantage of competing, especially in the face of The New Normal, for that there is a strategy needed in creating competitive advantages in The New Normal. The object of this research is small and medium enterprises in Magetan Regency. Data analysis techniques use descriptive analysis techniques. The results showed that competition between similar companies, the threat of new arrivals, the threat of replacement products, the bargaining power of buyers, and the bargaining power of suppliers are problems faced by small and medium enterprises in Magetan Regency.